An efficient regeneration protocol from callus culture in rough lemon (Citrus jambhiri) - KUMAR, KRISHAN; KAUR, H; GILL, M I S; RATTANPAL, H S; KANIKA, KANIKA; GOSAL, S S (The Indian Journal of Agricultural Sciences, 2011)
A laboratory experiment was carried out during 2007–09 to develop an efficient and reliable regeneration protocol from callus cultures of rough lemon (Citrus jambhiri Lush.), a commercial citrus rootstock of India. Epicotyl segments and leaves excised from 3–4 weeks old in vitro-grown seedlings were used as explants for callus induction. Epicotyl segment was the most responsive explant and maximum callusing was induced on MS medium supplemented with naphthalene acetic acid [NAA (10.0 mg/litre)] + benzyl adenine [BA (1.0 mg/litre)] + kinetin [KIN (0.5 mg/litre)] + sucrose (6%) + galactose (3%). The percentage of regenerating calli and number of shoots per callus increased with increase in the concentration of BA from 1.0 to 3.0 mg/litre in the medium. Maximum shoot regeneration (76.09%) was achieved on MS medium supplemented with NAA (0.5 mg/litre) + BA (3.0 mg/litre) + KIN (0.5 mg/litre). Regeneration from callus was influenced by the carbohydrate composition of callus induction medium and its age. The regeneration potential was highest in the calli induced on medium supplemented with sucrose (6%) + maltose (2%) and it decreased progressively with increase in the age of callus from 40 to 120 days.